Accuracy of Rapid Diagnostic Test for Malaria Compared to Microscopy - Shah, Sanober; Waris, Jamal; Mushtaq, Hina; khan, Imran; Ali, Mashooque; Afridi, Nighat (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the diagnostic accuracy of the Rapid Diagnostic Test in the detection of malaria by taking routine microscopy as a gold standard.Study design: Cross-sectional study.Place and Duration of Study: Department of Haematology, Pakistan Naval Ship Rahat Hospital, Karachi Pakistan, from Aug 2018 to Jan 2019.Methodology: Patients diagnosed as a case with malaria were included. Malaria was confirmed by using a Rapid detection test and microscopy. Mean and standard deviations were calculated for the quantitative variables like age. Frequencies and percentages were calculated for the qualitative variables like gender. Sensitivity, specificity, positive predictive value, negative predictive value and diagnostic accuracy were calculated.Results: Out of 175 patients in the study, the mean age was 39.30 ± 11.29 years. 85 (48.6%) were male, and 90 (51.4%) were female. Out of 175 patients, sensitivity, specificity, positive predictive value, negative predictive value and diagnostic accuracy of the rapid diagnostic test for malaria, keeping microscopy as the gold standard was found to be 87.2%, 74.15%, 67.34%, 85.71% and 80.57% respectively.Conclusion: Rapid immune-capture tests can have excellent applicability in malaria diagnosis. Field workers can reliably read such tests without any supervision. It appears to satisfy the desired criteria of being rapid, easy to perform, interpret and reasonably accurate.